ترجمة التعبير الإصطلاحي المعلق بالأفعال المتعدية بحرف جر في كتاب وصف الجنة والنار لوحيد عبد السالم بالي - Fatikhin, Roro (Journal of Arabic Language and Literature (ALLAIS), 2022)
The translation is a process of transferring messages from one language to another by looking at the structure and context that exists in the original language and the target language. With the translation process, a nation can recognize the existence of the culture and character of other nations. So that between the two cultures will not easily misunderstand their respective cultures. The main problem that we often encounter in translation is that in the source language, in this case Arabic, it has many forms of verbs that have many meanings in the target language, so that the process of transferring messages in the target language requires a good accuracy of selection. The exact meaning and equivalent of words in the target language. Therefore, the author will try to find the meaning of these words by using a semantic approach in order to obtain better translation results in accordance with the existing context. The semantic theories that will be used by the author include: Lexicon Semantic Theory, Grammatical Semantics, and Contextual Semantics. From this research, the writer found that many verbs were connected with the letter jar and then gave rise to new, more contextual meanings.